2011
DOI: 10.1093/europace/eur165
|View full text |Cite
|
Sign up to set email alerts
|

Risk markers of late high-degree atrioventricular block in patients with left ventricular dysfunction after an acute myocardial infarction: a CARISMA substudy

Abstract: Late HAVB development in post-AMI patients with left ventricular dysfunction can be predicted by risk stratification tests. Measures of HRV reflecting autonomic dysfunction revealed the highest predictive capabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…In HRV analysis of healthy individuals, the value of is close to one in young adults, and gradually increases with aging [59]. Moreover, an abnormal increase of (9 1.5) has been reported to be associated with an increased risk of mortality in cardiac patients [61], [62]. To consider this phenomenon, it is important to note that the long-range correlated nature over the range of several tens of seconds to a few hours arises from endogenous HRV dynamics, not from exogenous effects such as behavioral and environmental factors [26].…”
Section: B Frequency Domain Hrv Markers and The Limitationsmentioning
confidence: 89%
See 1 more Smart Citation
“…In HRV analysis of healthy individuals, the value of is close to one in young adults, and gradually increases with aging [59]. Moreover, an abnormal increase of (9 1.5) has been reported to be associated with an increased risk of mortality in cardiac patients [61], [62]. To consider this phenomenon, it is important to note that the long-range correlated nature over the range of several tens of seconds to a few hours arises from endogenous HRV dynamics, not from exogenous effects such as behavioral and environmental factors [26].…”
Section: B Frequency Domain Hrv Markers and The Limitationsmentioning
confidence: 89%
“…With regards to a dynamical disease perspective [ Fig. 1], the following aspects of the HRV dynamics should be considered as important: (1) common dynamical properties of HRV have been observed in healthy subjects even in daily life, when the measurements are performed, [23], [26], although these properties can depend on age [59], [60]; (2) these properties arise from endogenous HRV dynamics, not from behavioral and environmental factors [23], [26]; and (3) an alteration of such properties are associated with morbidity and mortality in cardiac patients [25], [28], [61], [62]. These properties have been observed in long-range correlation [26], multifractality [22] and scale invariant non-Gaussianity [23].…”
Section: Heart Rate Variabilitymentioning
confidence: 99%
“…In addition, the frequently visit by their family members and friends may lead to insufficient rest and sleep of patients. [14]. Early use of anti-arrhythmic drugs or the implantation of a temporary pace-maker following AMI are essential for the prevention and treatment of arrhythmia.…”
Section: Discussionmentioning
confidence: 99%
“…The study also showed that development of intermittent highdegree AV block was the best predictor of mortality. 4,5 The implications of the CARISMA study will be further elucidated with a subsequent study utilizing a newer ILR with enhanced atrial arrhythmia diagnostics. These studies will further demonstrate how continuous monitoring with implantable devices can improve the understanding of cardiovascular outcomes post-myocardial infarction and provide a better understanding of the efficacy of current and future therapies.…”
Section: Risk Stratification Post-myocardial Infarctionmentioning
confidence: 99%
“…[1][2][3] In addition to being a useful diagnostic tool for syncope, multiple clinical studies are evaluating the utility of ILR for tailored therapy of atrial fibrillation (AF) rhythm or rate control strategy and anticoagulation regimens, for improving the outcomes of patients with cryptogenic stroke (CS), and for risk stratification after a myocardial infarction. 4,5 This article reviews ILR technology, implantation technique and complications, clinical indications and limitations, cost and reimbursement, and future developments.…”
Section: Introductionmentioning
confidence: 99%